Recycling of Spent Mushroom Substrate for the Production of Oyster Mushroom - Ashrafi, R; Mian, M. H.; Rahman, M.M.; Jahiruddin, M. (Research in Biotechnology, 2014)
The huge amount of spent mushroom substrate (SMS) was disposed, especially around the mushroom cultivation complexes. The present study aimed at utilizing this SMS in a productive and sustainable way. Experiment was carried out to reuse of SMS of oyster mushroom for the production of oyster mushroom at Bangladesh Agricultural University (BAU), Mymensingh. Two mushroom species (Pleurotus ostreatus and P. florida) were grown on SMS supplemented with sawdust and wheat bran at different proportions. The results showed that SMS supplement with 60% sawdust + 20% wheat bran demonstrated the highest biological yield, economic yield and biological efficiency for both P. ostreatus and P. florida. Yield parameters were increased with increasing C/N ratio where as 36:1 C/N ratio exhibited the highest yield. The C/N ratio below or above 36:1 decreased yield of both species of oyster mushroom. The optimum C/N ratio for economic yield varied between the two oyster mushroom species and found to be 35.2 for P. ostreatus against C/N ratio of 40.1 for P. florida. Concerning biological yield and biological efficiency the optimum C/N ratio was found 35.7 for P. Ostreatus and 40.6 for P. florida. The study emphatically indicated that reuse of spent mushroom substrate with supplementation can be a good solution to address the disposal problem where as supplemented SMS can be a good substrate for further mushroom production.